(untitled) (The International Journal of Educational Sciences and Arts, 2023)
The title of the research: Characteristics of artistic expression in the drawings of art education teachers’ children and children of other teachers. The research problem was determined by the following question: Are there similar and different characteristics in drawings of children of art education teachers and other teachers? The research aims to identify the characteristics of artistic expression in the drawings of art education teachers’ children and children of other teachers. The research limits are kindergarten children at the age of (4-5) years, kindergartens in Najaf Governorate (the centre), the second chapter is the theoretical framework and previous studies, and the third chapter is the research procedures. The research community, the research sample, and the statistical methods. The researcher relied on children’s drawings, which amounted to (60) drawings, and the research sample (40) drawings for each of the drawings of children of art education teachers and children of other teachers. Rely on results, conclusions, recommendations, suggestions and sources.